Triboelectric behaviour of selected MOFs in contact with metals - Šutka, Andris; Shieh, Fa-Kuen; Kinka, Martynas; Lapčinskis, Linards; Chang, Chien-Chun; Lam, Phuc Khanh; Pudzs, Kaspars; Verners, Osvalds (Royal Society of Chemistry, 2022)
MOFs have been effectively used to magnify the triboelectric charge of polymers. However, so far the individual triboelectric properties and charge transfer mechanisms of MOFs haven't been reported. Triboelectric property investigation for selected MOFs show that the main mechanism for MOF triboelectrification in contact with metals is electron transfer. © 2023 The Royal Society of Chemistry.--//-- This is an open access article Šutka A., Shieh F.-K., Kinka M., Lapčinskis L., Chang C.-C., Lam P.K., Pudzs K., Verners O., "Triboelectric behaviour of selected MOFs in contact with metals" (2022) RSC Advances, 13 (1), pp. 41 - 46, DOI: 10.1039/d2ra06150c published under the CC BY and CC BY-NC licence.
This work was funded by Latvian-Lithuanian-Taiwan Scientific Cooperation Support Fund (LV-LT-TW/2021/3) represented by the Research Council of Lithuania (Project Nr. S-LLT-21-2) and Latvian Council of Science (Project Nr. 03000-3.1.2.1-e/3). Fa-Kuen Shieh would like to thank the Ministry of Science and Technology, Taiwan, for funding support (MOST 110-2923-M-008-002-MY3). Part of the measurements were performed on equipment located at the Center of Excellence at the Institute of Solid State Physics, University of Latvia, which is supported by European Union's Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under Grant Agreement No. 739508, project CAMART2. O. Verners acknowledges support by the European Regional Development Fund within the Activity 1.1.1.2 “Post-doctoral Research Aid” of the Specific Aid Objective 1.1.1 “To increase the research and innovative capacity of scientific institutions of Latvia and the ability to attract external financing, investing in human resources and infrastructure” of the Operational Programme “Growth and Employment” (No.1.1.1.2/VIAA/4/20/636). O. Verners acknowledges Riga Technical University's HPC Center for providing access to their computing infrastructure.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics